First live birth in China after cryopreserved ovarian tissue transplantation to prevent premature ovarian insufficiency. (4th July 2022) - Ruan, X.; Du, J.; Lu, D.; Duan, W.; Jin, F.; Kong, W.; Wu, Y.; Dai, Y.; Yan, S.; Yin, C.; Li, Y.; Cheng, J.; et al.
Abstract: Objective: This article reports the first live birth after cryopreserved ovarian tissue transplantation to prevent premature ovarian insufficiency in China. Methods: A patient with myelodysplastic syndrome received ovarian tissue cryopreservation before hematopoietic stem cell transplantation, and six ovarian cortex strips were thawed and transplanted into her peritoneal pocket 2 years later. Results: Pregnancy occurred spontaneously 27 months after grafting, and a healthy girl was born at 38 weeks gestation. Until now, the child has developed normally without any major diseases. Conclusions: We report the first live birth resulting from ovarian tissue cryopreservation and transplantation in China.